2020
DOI: 10.1111/bju.15288
|View full text |Cite
|
Sign up to set email alerts
|

Impact of circulating microRNA test (miRNA‐371a‐3p) on appropriateness of treatment and cost outcomes in patients with Stage I non‐seminomatous germ cell tumours

Abstract: Objectives To determine whether utilisation of a serum microRNA (miRNA) test could improve treatment appropriateness and cost‐effectiveness for patients with Stage I non‐seminomatous germ cell tumours (NSGCTs). Patients and Methods A decision tree model was built to investigate treatment course, clinical and cost outcomes for patients with Stage IA (T1N0M0S0) and IB (T2–4N0M0S0) NSGCT. The model compared outcomes and cost of standard approach using histopathology, conventional serum tumour markers and radiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Finally, we also tested an additional setting of relevance, which is the follow-up of these patients (57). Follow-up routinely involves repeat measurements of classical serum tumor markers (which show important limitations in detecting relapses) and continuing imaging [both costly, with limited sensitivity for very small metastatic deposits and exposing young patients to radiation if computed tomography is performed (30,58,59)]. In this sense, hsa-miR-371a-3p measurements are attractive for adequate monitoring and for guiding treatment decisions (34).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we also tested an additional setting of relevance, which is the follow-up of these patients (57). Follow-up routinely involves repeat measurements of classical serum tumor markers (which show important limitations in detecting relapses) and continuing imaging [both costly, with limited sensitivity for very small metastatic deposits and exposing young patients to radiation if computed tomography is performed (30,58,59)]. In this sense, hsa-miR-371a-3p measurements are attractive for adequate monitoring and for guiding treatment decisions (34).…”
Section: Discussionmentioning
confidence: 99%
“…miR-371a-3p has emerged as the most remarkable non-invasive biomarker for diagnosis and follow-up of TGCT patients, as demonstrated by several retrospective and also prospective works by various groups [13][14][15][16][17] (for a recent review see [18]). Its introduction in the clinic is to occur soon and may reduce costs in patient follow-up [19]. However, its major limitation is the inability to detect a subset of NS, which is teratoma (TE) [17,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…38 Finally, Bagrodia et al, built a decision tree model for CS IA and IB NSGCTs comparing histopathology, conventional STMs and imaging (Standard model) versus the standard model + miR371a-3p. 39 They reported that by using the miRNA marker-based approach, 26% of patients avoid overtreatment and 8% avoid undertreatment in CS IA, and 27% avoid overtreatment and 23%undertreatment in Clinical…”
Section: Clinical Stage I-early Stagingmentioning
confidence: 99%
“…They reported that by using the miRNA marker‐based approach, 26% of patients avoid overtreatment and 8% avoid undertreatment in CS IA, and 27% avoid overtreatment and 23%undertreatment in Clinical Stage IB (CS IB). Also, the accuracy of traditional TGCTs staging might increase from 65% to 94% for CS IA and from 50% to 92% for CS IB 39 . However, it should be noted this model was created before we published our data that more accurately depicts the performance characteristics of post‐orchiectomy miR‐371a‐3p in CS I disease 15 .…”
Section: Introductionmentioning
confidence: 99%